RESPON KOMUNITAS RELIGIUS TERHADAP PANDEMIC COVID-19 DALAM TINJAUAN EPISTEMOLOGI - Marlin C. Laimeheriwa C Laimeheriwa (DIALEKTIKA, 2021)
The Covid 19 pandemic has been successfully terrorized the entire world community. Every community and individual has had a strategy to survive the Covid 19 pandemic. This article discusses the response of the religious community to the Covid 19 pandemic i n an epistemological overview, which is a model of knowledge possessed by religious communities. This paper uses qualitative data in the form of literature and media data as material objects regarding the response of the religious community during the pandemic. The results obtained from online media and literature studies show three types of knowledge, namely: first, scientific knowledge in the form of a response from the religious community which accepts scientific facts about Covid 19; second, religious knowledge has always been the basis for facing the Covid 19 pandemic; third, religious communities based on scientific and religious knowledge also develop moral knowledge. These three types of knowledge are intertwined in every response of the religious community.